Mir-pharmacogenetics of Vincristine and peripheral neurotoxicity in childhood B-cell acute lymphoblastic leukemia. Issue 6 (December 2018) - Gutierrez-Camino, Ángela; Umerez, Maitane; Martin-Guerrero, Idoia; García de Andoin, Nagore; Santos, Borja; Sastre, Ana; Echebarria-Barona, Aizpea; Astigarraga, Itziar; Navajas, Aurora; Garcia-Orad, Africa
Abstract Vincristine (VCR), an important component of childhood acute lymphoblastic leukemia (ALL) therapy, can cause sensory and motor neurotoxicity. This neurotoxicity could lead to dose reduction or treatment discontinuation, which could in turn reduce survival. In this line, several studies associated peripheral neurotoxicity and polymorphisms in genes involved in pharmacokinetics (PK) and pharmacodynamics (PD) of VCR. Nowadays, it is well known that these genes are regulated by microRNAs (miRNAs) and SNPs in miRNAs could modify their levels or function. Therefore, the aim of this study was to determine whether SNPs in miRNAs could be associated with VCR-induced neurotoxicity. To achieve this aim, we analyzed all the SNPs in miRNAs (minor allele frequency (MAF) ≥ 0.01) which could regulate VCR-related genes in a large cohort of Spanish children with B-cell precursor ALL (B-ALL) homogeneously treated with LAL/SHOP protocols. We identified the A allele of rs12402181 in the seed region of miR-3117-3p, that could affect the binding withABCC1 andRALBP1 gene, and C allele of rs7896283 in pre-mature sequence of miR-4481, which could be involved in peripheral nerve regeneration, significantly associated with VCR-induced neurotoxicity. These findings point out the possible involvement of two SNPs in miRNA associated with VCR-related neurotoxicity.